Sectional Analysis of Reinforced Engineered Cementitious Composite Columns Subjected to Combined Lateral Load and Axial Compression - Wu, Chang; Su, Yanli; Sun, Yu; Jin, Chenhua; Pan, Zuanfeng (Frontiers in Materials, 2022)
The ultra-high tensile ductility of ECC provides an alternative way to enhance the ductility of the structural members by using high ductile matrix material instead of simply increasing reinforcements. However, the application of ECC members is still limited due to the relatively short research time and the lack of design specifications. Being equivalent to eccentric compressive members, a sectional analysis of RECC columns subjected to combined lateral load and axial compression were proposed in this paper. On the basis of the design theory of load capacity of eccentric compression columns and unique constitutive model of ECC, the calculation equations for the sectional load capacity of RECC columns were derived. The analytical prediction of the load capacity of RECC column was evaluated in comparison with that of experiments which confirmed the capacity of the proposed calculation method to capture the behavior of RECC column accurately. The strength interaction diagrams showing the axial force-moment (N-M) interaction curves were then constructed for analysis using the proposed calculation equations. A parametric study was also carried out by using proposed calculation equations, demonstrating the effects of ultimate tensile strain of ECC, compressive and tensile strength of ECC, yield strength of steel bar and reinforcement ratio on the N-M interaction curves of RECC columns. The investigations exhibited in this paper are expected to provide insight on the design principles of RECC columns.